2011
DOI: 10.5539/ibr.v5n1p164
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization and Capital Structure of Taiwan Electronic Corporations

Abstract: This paper analyzes capital structure between the internationalized and domestic electronic industries in Taiwan from 1999 to 2008 as the reference for financing strategies and decision. The evidence shows that the leverage and the payout cash dividend ratio in the internationalized electronic firms are lower than those in domestic electronic firms. Due to the uniqueness and the high profit ability of the internationalized electronic firms in the Taiwan, they have more earnings and inside capital so that the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…The findings are consistent with the studies done by Burgman (1996), Low and Chen (2004), Aggarwal and Kyaw (2010) and Lin and Hung (2012). Burgman (1996) and Low and Chen (2004) investigated and revealed that the negative relationship between internationalization and debt ratio is mainly attributed to US firms.…”
Section: Internationalizationsupporting
confidence: 90%
See 2 more Smart Citations
“…The findings are consistent with the studies done by Burgman (1996), Low and Chen (2004), Aggarwal and Kyaw (2010) and Lin and Hung (2012). Burgman (1996) and Low and Chen (2004) investigated and revealed that the negative relationship between internationalization and debt ratio is mainly attributed to US firms.…”
Section: Internationalizationsupporting
confidence: 90%
“…Thus, leverage of these firms would decrease. It is supported by the studies by Aggarwal and Kyaw (2010) and Lin and Hung (2012) as their research results indicated that internationalized firms generate greater profitability and have lower debt ratio compared to domestic firms. The inverse relationship between internationalization and debt ratio is also consistent with the implications of agency theory.…”
Section: Internationalizationmentioning
confidence: 69%
See 1 more Smart Citation
“…Regarding studies of the relationship between multinational and local companies' debt structure; Hughes, Logue, and Sweeney (1975), Shapiro (1978), Lee and Kwok (1988), Burgman (1996), Kwok and Reeb (2000), and Lin and Hung (2012) indicate that the borrowing rate of multinational companies is lower than that of domestic companies. Greenaway, Guariglia and Kneller (2007) states that the debt ratio of exporting firms is less than that of non-exporting firms.…”
Section: Introductionmentioning
confidence: 99%
“…This means Companies that have high asset growth will tend to use more debt; this is because companies with a high growth rate of the capital need relatively large, so the company will rely on the use of external funds in the form of debt. According to Lin and Hung (2012), the company that wants great growth opportunities requires considerable funding for expansion cannot rely on internal funds are limited, so the company can borrow funds from external parties to fund the company's activities. This is consistent with the pecking order theory; companies will prioritize the use of internal funds first, if not sufficient it will take the form of debt financing sources to issue shares.…”
Section: Hypothesis Test (T-test)mentioning
confidence: 99%